Efficacy of alternative or adjunctive measures to conventional non-surgical and surgical treatment of peri-implant mucositis and peri-implantitis: a systematic review and meta-analysis - Ausra Ramanauskaite (SpringerOpen, 2021)
Abstract Purpose To evaluate the efficacy of alternative or adjunctive measures to conventional non-surgical or surgical treatment of peri-implant mucositis and peri-implantitis. Material and methods Prospective randomized and nonrandomized controlled studies comparing alternative or adjunctive measures, and reporting on changes in bleeding scores (i.e., bleed0ing index (BI) or bleeding on probing (BOP)), probing depth (PD) values or suppuration (SUPP) were searched. Results Peri-implant mucositis: adjunctive use of local antiseptics lead to greater PD reduction (weighted mean difference (WMD) = − 0.23 mm; p = 0.03, respectively), whereas changes in BOP were comparable (WMD = − 5.30%; p = 0.29). Non-surgical treatment of peri-implantitis: alternative measures for biofilm removal and systemic antibiotics yielded higher BOP reduction (WMD = − 28.09%; p = 0.01 and WMD = − 17.35%; p = 0.01, respectively). Surgical non-reconstructive peri-implantitis treatment: WMD in PD amounted to − 1.11 mm favoring adjunctive implantoplasty (p = 0.02). Adjunctive reconstructive measures lead to significantly higher radiographic bone defect fill/reduction (WMD = 56.46%; p = 0.01 and WMD = − 1.47 mm; p = 0.01), PD (− 0.51 mm; p = 0.01) and lower soft-tissue recession (WMD = − 0.63 mm; p = 0.01), while changes in BOP were not significant (WMD = − 11.11%; p = 0.11). Conclusions Alternative and adjunctive measures provided no beneficial effect in resolving peri-implant mucositis, while alternative measures were superior in reducing BOP values following non-surgical treatment of peri-implantitis. Adjunctive reconstructive measures were beneficial regarding radiographic bone-defect fill/reduction, PD reduction and lower soft-tissue recession, although they did not improve the resolution of mucosal inflammation.